Evauation of flax (Linum unitatissimum) genotypes for multipal-disease resistance - BASANDRAI, DAISY; BASANDRAI, ASHWANI K; SETHI, G S; BHATERIA, S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1989 and 1990 to study multiple-disease resistance in 200 indigenous lind exotic stocks of flax (Linum usitatissimum L.). The genotypes were evaluated for resistance to flax rust [Melampsora lini (Pers.) Lev.], wilt [Fusarium oxysporum f sp lini (Bolley) Snyder & Hansen] and powdery mildew (oidium limi Skoric) to identify disease-resistant genotypes having desirable agro- morphological characters of fibre flax. out of these, 139, 35 and 24 genotypes were free from rust, wilt and powdery mildew respectively. In all 22 genotypes were free from or resistant to all the 3 diseases. Twelve genotypes ('Aoyogi', 'Belinka', 'Buchara Brazoio A', 'Crocus', 'EC 278967', 'EC 278980', 'EC 278981', 'EC 278985', 'EC 278987', 'EC 278990', 'Flak l' and 'L 1325') resistant to the diseases had desirable plant height for fibre flax. These genotypes may be exploited in further breeding programme.